Trends in mortality inequalities in an urban area: the influence of immigration - Maica Rodríguez-Sanz; Mercè Gotsens; Marc Marí dell'Olmo; Carme Borrell (BMC, 2019)
Abstract Background Nearly 20% of the population in Barcelona is foreign-born and this percentage rises to up to 40% in some neighborhoods. Consequently, migration health patterns may play an important role in trends in socioeconomic geographical inequalities in mortality. The objective of this study was to analyze the trend in socioeconomic inequalities in mortality between neighborhoods in Barcelona during the period 2001-2012 in the foreign-born and Spanish-born population. Methods Repeated cross-sectional design of the population aged 25-64 years in Barcelona between 2001 and 2012. Hierarchical data consisted of yearly mortality linked-population. The variables analyzed were age, sex, education, and country of birth (Spanish-born, foreign-born), neighborhood of residence, and the socioeconomic level of the neighborhoods using quartiles of unemployment rates. Age-standardized mortality rates were estimated, and mixed Poisson regressions were applied using generalized linear mixed models, including two random effects to consider the intracorrelation within neighborhoods and across years. Results The number of foreign-born residents aged 25-64 increased notably in disadvantaged neighborhoods. Approximately 9% of premature deaths occurred in foreign-born individuals. Premature mortality rates were higher in disadvantaged neighborhoods and in the Spanish-born population in all periods. Despite the stabilized socioeconomic inequalities in mortality in the Spanish-born population, no inequalities were found between neighborhoods in foreign-born men and women. Conclusions Evidence of the 'healthy migrant' effect in mortality and socioeconomic inequalities in mortality was found in Barcelona, which seems to alter the distribution of mortality through time and space, related to the low levels of premature mortality and the selective residence of immigrants in socioeconomically disadvantaged neighborhoods.